PENGARUH KONTEN VIDEO PEMASARAN DAN REVIEW PRODUK TERHADAP MINAT BELI SEPATU VENTELA DI TIKTOK - Bagas santoso, Nico Alviano; Siswanto, Udin; Ardiansyah, Fitra; Kusmayati, Nindya Kartika (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
The purpose of this study is to determine how marketing video content and product reviews found on the TikTok platform influence consumers' purchase intentions toward Ventela brand shoes in their vicinity. TikTok, as a short-form video-based social media platform, can influence users through engaging and interactive visual content. This research employs a quantitative method using IBM SPSS Version 3.0 and involves 52 respondents who actively use TikTok. Data was gathered by means of a survey. Validity tests, partial tests (t-tests), and linear regression analysis were used to assess each variable's impact. The findings show that while product reviews do not significantly affect purchase intention (significance value 0.253 > 0.05), marketing video material does (significance value 0.001 < 0.05). Y = 1.544 + 0.816X1 + 0.144X2 + e. is the equation derived from the linear regression test. The results indicate that video-based marketing strategies are more successful than product reviews alone at generating customer interest in making purchases. As a result, brands are encouraged to improve the quality of their video content and pair it with reliable product reviews to boost the efficacy of their digital marketing strategies. This study found that video content on TikTok significantly influences consumers’ intention to purchase local products.